“Apostles of the Liberalmarxism”: Framing of the “Left” in the Right-wing Lithuanian Discourse - Jonutis, Karolis; Davidavičius, Algirdas (Politologija, 2023)
Although it is often argued that left/right distinction in modern politics doesn’t matter anymore, yet public discourse is still full of references addressed to ideologically named opponents. The aim of this paper is to analyze how conception of left-wing ideology (its characteristics and contextualization) in Lithuanian public right-wing discourse is constructed to form coherent discourse of imaginary left. Ervin Goffman’s and Marvin Minsky’s frame analysis theoretical perspective is used to analyze framing of left-wing discourse in three levels: meta-, mezzo- and micro-. Discourse analysis method is used in research.